Proceedings of the 5th International Symposium on Biological Control of Arthropods - Vincent, Charles; Gillespie, David R.; Mason, Peter (CABI, 2023)
This proceedings contains papers dealing with issues affecting biological control, particularly pertaining to the use of parasitoids and predators as biological control agents. This includes all approaches to biological control: conservation, augmentation, and importation of natural enemy species for the control of arthropod targets, as well as other transversal issues related to its implementation. It has 14 sessions addressing the most relevant and current topics in the field of biological control of arthropods: (i) Accidental introductions of biocontrol agens: positive and negative aspects; (ii) The importance of pre and post release genetics in biological control; (iii) How well do we understand non-target impacts in arthropod biological control; (iv) Regulation and access and benefit sharing policies relevant for classical biological control approaches; (v) The role of native and alien natural enemy diversity in biological control; (vi) Frontiers in forest insect control; (vii) Biocontrol marketplace I; (viii) Weed and arthropod biological control: mutual benefits and challenges; (ix) Maximizing opportunities for biological control in Asia's rapidly changing agro-environments; (x) Biological control based integrated pest management: does it work?; (xi) Exploring the compatibility of arthropod biological control and pesticides: models and data; (xii) Successes and uptake of arthropod biological control in developing countries; (xiii) Socio-economic impacts of biological control; (xiv) Biocontrol marketplace II.